Clonal dissemination of carbapenem-resistant ST477 Klebsiella michiganensis co-producing NDM-1, SFO-1, and VEB-3 in a Chinese hospital - Liu, Hao; Yan, Chao; Jiao, Meiling; Jiang, Juntian; Wang, Sibo; Wei, Zhuo; Hu, Fupin; Xu, Xuesong (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesTo investigate the antimicrobial resistance mechanisms and intra-hospital clonal dissemination of carbapenem-resistant ST477 Klebsiella michiganensis.MethodsBetween 14 December 2019 and 23 August 2020, six K. michiganensis isolates producing NDM-type carbapenemases were recovered from Jilin Provincial People’s Hospital in China. Antimicrobial susceptibility was determined using the broth microdilution method. Whole-genome sequencing (WGS) was performed for all isolates. Sequence typing (ST), resistance genes, and plasmid types were identified using the PubMLST, ResFinder, and PlasmidFinder databases, respectively. Conjugation experiments were conducted to assess plasmid transferability. Additionally, 344 publicly available K. michiganensis genomes were retrieved and used to construct a phylogenetic tree based on core-genome single nucleotide polymorphisms (SNPs).ResultsWGS revealed that all six isolates belonged to ST477 and harbored blaNDM-1, blaSFO-1, and blaVEB-3. The maximum pairwise difference among the six isolates was only 8 SNPs, indicating clonal transmission. Antimicrobial susceptibility testing showed high-level resistance to imipenem, meropenem, and ceftazidime-avibactam, while susceptibility was retained to amikacin, aztreonam-avibactam, eravacycline, tigecycline, and colistin. Conjugation assays confirmed that the blaNDM-1-carrying plasmid was self-transmissible. Clinical data showed that four of the six patients had a history of transfer to the intensive care unit (ICU). Phylogenetic analysis combined with resistance gene profiling based on publicly available genomes revealed that 50% (175/350) of K. michiganensis isolates from human hosts carried carbapenem resistance genes. Notably, Isolates from China exhibited a higher carriage rate of carbapenemase genes (76.1%, 51/67). No ST477-related genomes were identified in current public datasets.ConclusionsThis study is the first to report the clonal dissemination of ST477 K. michiganensis harboring blaNDM-1 in a Chinese hospital.